EXPERIMENTAL STUDY OF SOME GEOMETRIC AND ENERGY PARAMETERS OF BETULIN (Conference Zone, 2021)
In this study, the results of the study of some geometric and energy parameters of betulin by empirical methods using the Avagadro program are presented